2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.24709
|View full text |Cite
|
Sign up to set email alerts
|

Simple Ways so Facilitate Active Learning in Hands-on Electrical Engineering Technology Courses

Abstract: The traditional way engineering and engineering technology courses are taught is based on traditional lecture and laboratory experiments, which are still the most frequent teaching methods used nowadays around the world. On the other hand, active learning methodologies grounded in scientific research in education have been attracting considerable attention over the past years with numerous research studies indicating the efficacy of such learning styles.In this article, the author addresses the main challenges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…Oliveira adopted active learning approaches to encourage active learning and engagement among students in face-to-face electrical engineering technology courses. The assessment results demonstrated that the active learning strategies have successfully met the teaching requirements (Oliveira, 2015). Cooperative learning activities promote peer interaction and assist the development of engineering course in terms of better learning of concepts and content.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…Oliveira adopted active learning approaches to encourage active learning and engagement among students in face-to-face electrical engineering technology courses. The assessment results demonstrated that the active learning strategies have successfully met the teaching requirements (Oliveira, 2015). Cooperative learning activities promote peer interaction and assist the development of engineering course in terms of better learning of concepts and content.…”
Section: Introductionmentioning
confidence: 91%
“…To achieve these learning outcomes in engineering education, a variety of pedagogical considerations have been implemented and experimented, such as inquiry-based learning (Behrouzi and Kuchma, 2016), project-based learning (Khorbotly, 2015;Wang et. al., 2017;, cooperative learning (Akili, 2012), active learning Akili, 2014;Oliveira, 2015), divide-and-conquer learning (Kos and Miller, 2017; Sullivan-Green, et. al., 2017), studentcentered learning (Grigg and Stephan, 2018), and problem-based method (Oliveira, 2015), etc.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To achieve these learning outcomes in engineering education, a variety of pedagogical considerations have been implemented and experimented. There have been a large number of pedagogical efforts proposed and implemented, such as inquiry-based learning (Behrouzi and Kuchma, 2016), project-based learning (Khorbotly, 2015;, cooperative learning (Akili, 2012), active learning Akili, 2014;Oliveira, 2015), divide-and-conquer learning (Kos and Miller, 2017; Sullivan-Green, et. al., 2017), student-centered learning (Weimer 2002;Grigg and Stephan, 2018), and problem-based method (Oliveira, 2015), etc.…”
Section: Introductionmentioning
confidence: 99%